2013
DOI: 10.1111/eve.12021
|View full text |Cite
|
Sign up to set email alerts
|

Transitional cell carcinoma of the urinary bladder in a 12‐year‐oldBelgianWarmblood gelding

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
3
0
5
Order By: Relevance
“…Neoplasia of the urinary tract was considered most likely at the time of initial evaluation at the VTH, although the appearance of the bladder mucosa was not consistent with previously described bladder neoplasms. Squamous cell carcinoma (Fischer et al 1985;Serena et al 2009), transitional cell carcinoma (Lisowski et al 2015), lymphosarcoma (Sweeney et al 1991;Meyer et al 2006) and leiomyosarcoma (Hurcombe et al 2008) have been reported as causes of haematuria in horses, although they are typically associated with difficulty urinating and/or systemic illness which was not evident in this patient. Other differentials included benign fibromatous/fibroepithelial polyps (Fischer et al 1985), urothelial papilloma or polypoid formation secondary to cystitis, although the latter two have not been previously described in horses (Tsuzuki and Epstein 2005).…”
Section: Differential Diagnosesmentioning
confidence: 67%
“…Neoplasia of the urinary tract was considered most likely at the time of initial evaluation at the VTH, although the appearance of the bladder mucosa was not consistent with previously described bladder neoplasms. Squamous cell carcinoma (Fischer et al 1985;Serena et al 2009), transitional cell carcinoma (Lisowski et al 2015), lymphosarcoma (Sweeney et al 1991;Meyer et al 2006) and leiomyosarcoma (Hurcombe et al 2008) have been reported as causes of haematuria in horses, although they are typically associated with difficulty urinating and/or systemic illness which was not evident in this patient. Other differentials included benign fibromatous/fibroepithelial polyps (Fischer et al 1985), urothelial papilloma or polypoid formation secondary to cystitis, although the latter two have not been previously described in horses (Tsuzuki and Epstein 2005).…”
Section: Differential Diagnosesmentioning
confidence: 67%
“…Immunohistochemical examination of endoscopically obtained tissue from a cystic carcinoma can identify whether the neoplastic cells express COX‐2 receptors, thereby determining if treating the horse with a COX‐2 selective NSAID might be effective (Lisowski et al . ; Busechian et al . ).…”
Section: Conditions Associated With Haematuria In the Horse And Cluementioning
confidence: 99%
“…Urolithiasis, primary cystitis (Fig 2) (Smith et al 2016), mucosal ulceration associated with chronic administration of a NSAID (Aleman et al 2011), exercise-induced mucosal erosions in the bladder (Schott 2002), cystic neoplasia (Fischer et al 1985;Patterson-Kane et al 2000;Hurcombe et al 2008;Serena et al 2009;Busechian et al 2016) and polypoid cystitis (Rosales et al 2019) can be identified during cystoscopy. Immunohistochemical examination of endoscopically obtained tissue from a cystic carcinoma can identify whether the neoplastic cells express COX-2 receptors, thereby determining if treating the horse with a COX-2 selective NSAID might be effective (Lisowski et al 2015;Busechian et al 2016).…”
mentioning
confidence: 99%
“…Der Harntrakt ist mit Übergangszellepithel (Epithelium transitionale) ausgekleidet, sodass ein TCC in jedem Abschnitt auftreten kann, am häufigsten beim Pferd jedoch in der Harnblasenwand (Fischer et al 1985, Turner et al 1995, Traub-Dargatz 1998, Patterson-Kane et al 2000, Lisowski et al 2015, Busechian et al 2016.…”
Section: Introductionunclassified
“…Die Masse hatte eine Größe von 4 × 6 cm und befand sich im Bereich des ventralen Blasenkörpers am Übergang zum Blasenhals. Lisowski et al (2015) präsentieren das erfolgreiche Kurzzeitergebnis durch chirurgisches Abtragen des Tumorgewebes ("surgical debulking") und orale Anwendung von Piroxicam. Die Masse hatte in diesem Fall eine Größe von 5 × 2,5 × 1,5 cm und befand sich im Bereich des Blasenhalses.…”
Section: Introductionunclassified